(untitled) (Practitioner Research, 2020)
Learning Management System (LMS) is becoming an important platform for university students. The use of LMS in teaching and learning process which focuses on the content subject has provided a wider opportunity for the TESL teacher trainees not only to apprehend the content but also to apply them in real life contexts. The study aims to unveil the usefulness of LMS in TESL teacher trainees’ learning of the content subject which is Second Language Acquisition (SLA). 15 participants (12 female, and 3 male) from one of the Teacher Training Institutes in the northern region of Malaysia participated in this qualitative case study. Participants were asked to write their personal reflections after each interaction using LMS. 15 weeks of classroom interactions were recorded for analysis. Participants had to write their reflections based on Pre-Class, While-Class and Post-Class Sessions. The findings were analyzed thematically based on the Seven Principles of Learning. The findings indicated that the participants were able to set their target in learning, they were aware of their learning styles, improved their skills and became more engaged in classroom activities. This study depicts the role of LMS in facilitating successful learning. It suggests that practitioners need to maximize the use of LMS for successful teaching and learning.